2013
DOI: 10.1097/mat.0b013e3182894351
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Minimized Extracorporeal Circulation on Outcome in Patients With Preoperative Anemia Undergoing Coronary Artery Bypass Surgery

Abstract: Preoperative anemia and low hematocrit during cardiopulmonary bypass have been associated with worse outcome in patients undergoing cardiac surgery. The minimized extracorporeal circulation (MECC) allows a reduction of the negative effects associated with conventional extracorporeal circulation (CECC). In this study, the impact of the MECC on outcome of anemic patients after coronary artery bypass grafting (CABG) was assessed. Between January 2004 and December 2011, 1,945 consecutive patients with preoperative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
3
0
5
Order By: Relevance
“…Previous studies have concluded that after mitral valve repair, minimal regurgitation is often undetected by intraoperative ultrasound [7]. Clinical evidence of hemolytic anemia usually manifests 90 days after surgery [7], but it may appear sooner, depending on the presence of certain factors that contribute to hemolysis; for example, for extracorporeal circulation through cardiopulmonary bypass, 12% hemolysis is estimated after 2 h on this mechanical system [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have concluded that after mitral valve repair, minimal regurgitation is often undetected by intraoperative ultrasound [7]. Clinical evidence of hemolytic anemia usually manifests 90 days after surgery [7], but it may appear sooner, depending on the presence of certain factors that contribute to hemolysis; for example, for extracorporeal circulation through cardiopulmonary bypass, 12% hemolysis is estimated after 2 h on this mechanical system [8]. …”
Section: Discussionmentioning
confidence: 99%
“…Канюляция восходящей аорты и правого предсердия осуществляется по общепринятой в кардио хирургии методике. Используется венозная двуступенчатая канюля 32/36-32/40 Fr [25,34,41,42] и аортальная канюля 20-24 Fr [25,34,41,43] в соответствии с площадью поверхности тела. Так как объемная скорость перфузии зависит от венозного притока [23], значение имеет корректное положение венозной канюли.…”
Section: канюляцияunclassified
“…Так, A. Hanea и соавт., а также другие исследователи эффективно использовали дозу 150 ед./кг [8,34,48]. Целевые значения ВАС при перфузии с MiECC должны составлять 250-300 с [43,49]. T. Puehler и соавт.…”
Section: антикоагуляцияunclassified
See 2 more Smart Citations